2010
DOI: 10.1007/s00198-010-1285-3
|View full text |Cite
|
Sign up to set email alerts
|

IOF position statement: vitamin D recommendations for older adults

Abstract: This position paper of the International Osteoporosis Foundation makes recommendations for vitamin D nutrition in elderly men and women from an evidencebased perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
373
0
55

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 653 publications
(434 citation statements)
references
References 18 publications
(19 reference statements)
6
373
0
55
Order By: Relevance
“…(2,3) Our trial has several strengths despite its small size. We had complete adherence to the study protocol and 100% of participants attended 14 clinical visits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2,3) Our trial has several strengths despite its small size. We had complete adherence to the study protocol and 100% of participants attended 14 clinical visits.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 2010 Institute of Medicine (IOM) recommendations support a 25(OH)D threshold of 20 ng/mL for bone health, (1) the International Osteoporosis Foundation, in their 2010 position paper on vitamin D, recommends a threshold of 30 ng/mL for optimal fall and fracture reduction, (2) consistent with the most recent recommendations by the U.S. Endocrine Society published in June 2011. (3) The recommendations by the International Osteoporosis Foundation (IOF) and the Endocrine Society are based on two meta-analyses of double-blind randomized controlled trials that suggested fall reduction required a threshold of at least 24 ng/mL (4) and fracture reduction a threshold of at least 30 ng/mL.…”
Section: Esirable Thresholds For 25(oh)d Have Been Discussedmentioning
confidence: 94%
See 1 more Smart Citation
“…Currently, there is no consensus on the optimum threshold concentration of 25(OH)D, but the Institute of Medicine (IOM) recommends a threshold of 50 nmol/L for bone health [3], whereas the International Osteoporosis Foundation (IOF) [4] and the Endocrine Society [5] recommend a threshold of 75 nmol/L for optimal reductions in fall or fracture risk. However, the question of whether this higher threshold is associated with improvements in other health outcomes remains controversial [6].…”
Section: -Hydroxy Vitamin D (25(oh)d) Is the Predominant Circulatinmentioning
confidence: 99%
“…In addition to the classical role of vitamin D in the maintenance of bone health, vitamin D deficiency has been associated with increased risks of a number of chronic conditions, including cardiovascular disease, diabetes, hypertension, some cancers, autoimmune diseases, and infectious diseases [3][4][5][6][7][8]. This growing awareness that adequate vitamin D status has potentially beneficial effects on a variety of health outcomes has led to a marked increase in research in this field.…”
Section: -Hydroxy Vitamin D (25(oh)d) Is the Predominant Circulatinmentioning
confidence: 99%